Pengaruh Kualitas Produk Dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Pondok Tince Palembang - annisa putri; Ratna Juwita (Universitas Multi Data Palembang, 2026)
This study aims to analyze the influence of product quality and service quality on customer satisfaction at Pondok Tince Palembang, both partially and simultaneously. This study applies a quantitative approach through a descriptive study type, which focuses on the presentation and analysis of the relationship between variables. Data collection was carried out by distributing questionnaires to 325 respondents selected as the research sample. The sample collection method applied was nonprobability sampling through a purposive sampling method, namely selecting respondents from certain criteria deemed relevant to the research objectives. The collected data were then analyzed to evaluate the magnitude of the influence of product quality and service quality on customer satisfaction. The findings of this study describe partially, each variable has a positive and significant influence on customer satisfaction. Simultaneously, product quality and service quality were also proven to contribute significantly to increasing customer satisfaction at Pondok Tince Palembang, making these two factors an important aspect in the restaurant's business strategy.